2023
DOI: 10.34133/research.0148
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Strategies for Overcoming Endosomal/Lysosomal Barrier in Nanodrug Delivery

Abstract: Nanocarriers have therapeutic potential to facilitate drug delivery, including biological agents, small-molecule drugs, and nucleic acids. However, their efficiency is limited by several factors; among which, endosomal/lysosomal degradation after endocytosis is the most important. This review summarizes advanced strategies for overcoming endosomal/lysosomal barriers to efficient nanodrug delivery based on the perspective of cellular uptake and intracellular transport mechanisms. These strategies include promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 201 publications
1
22
0
Order By: Relevance
“…These results indicated that the enhanced uptake efficiency of NPs might result from the CD44-mediated internalization, which is similar to that reported for the cell membrane of activated macrophages which usually overexpressed HA receptor (CD44) . The endosomal escape is also critical for the function of siRNA within recipient cells . To determine whether siRNA could escape from lysosomes following cellular uptake, intracellular fluorescence distribution of Cy5-siRNA-loaded NPs was observed by CLSM imaging.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These results indicated that the enhanced uptake efficiency of NPs might result from the CD44-mediated internalization, which is similar to that reported for the cell membrane of activated macrophages which usually overexpressed HA receptor (CD44) . The endosomal escape is also critical for the function of siRNA within recipient cells . To determine whether siRNA could escape from lysosomes following cellular uptake, intracellular fluorescence distribution of Cy5-siRNA-loaded NPs was observed by CLSM imaging.…”
Section: Resultssupporting
confidence: 78%
“…17 The endosomal escape is also critical for the function of siRNA within recipient cells. 21 To determine whether siRNA could escape from lysosomes following cellular uptake, intracellular fluorescence distribution of Cy5-siRNAloaded NPs was observed by CLSM imaging. Abundant colocalized fluorescence dots (yellow) were found in the cytoplasm after treating LPS-activated RAW 264.7 cells with AHK-CaP/Cy5-siRNA NPs for 3 h (Figure 2C), indicating that most of the siRNA (labeled in red) were still detained in the lysosomes (labeled in green) at the 3 h time point.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a, cells treated with free Dox showed strong red fluorescence of Dox in the nucleus after 1.5 h of culture. For the Dox-loaded micelles, we observed red fluorescence of Dox spread within the cytosol along with the weaker fluorescence in the nucleus after 1.5 h. Since the micelles are known to be taken up by cells via endocytosis and localize within endo/lysosomes, it is likely that the fluorescence observed in the nucleus is due to free Dox released from the micelles, while the fluorescence in the cytosol where endo/lysosomes exist is due to Dox encapsulated in the micelles. Therefore, the result indicates that the majority of Dox was maintained within the micelles after 1.5 h. On the other hand, after 3 h of culture, the fluorescence in the nucleus became intense compared to that in the cytosol, implying that a significant amount of Dox was released from the micelles.…”
Section: Resultsmentioning
confidence: 99%
“…185 One of the most difficult obstacles for gene delivery using a polymeric nanoparticulate approach is its endosomal entrapment, 186,187 and numerous efforts have been reported to overcome such barriers using a co-delivery approach. [188][189][190][191] Therefore, a polysaccharide-based cationic NG formed from cycloamylose bearing a hexadecyl group has been complexed with plasmid DNA and phospholipase A2 enzyme that further hydrolyses membrane phospholipids. When NG/phospholipase A2 complexes were targeted to cells, they were found to increase plasmid DNA expression levels and produce hemolytic activity the same as that of native phospholipase A2.…”
Section: Co-deliverymentioning
confidence: 99%